Reactivity and Bond Strength of Universal Dental Adhesives with Co-Cr Alloy and Zirconia - Dimitris Papadogiannis; Maria Dimitriadi; Maria Zafiropoulou; Maria-Dimitra Gaintantzopoulou; George Eliades (MDPI AG, 2019)
The aim of this study was to evaluate (a) the reactivity of six universal dental adhesives with polished cobalt-chrome (Co-Cr) alloy and zirconia (3Y-TZP) surfaces; and (b) to assess the shear bond strength (SBS) of a resin composite with polished and alumina-blasted surfaces as mediated by these adhesives. The products tested were Adhese Universal (AD), All-Bond Universal (AB), Clearfill Universal Bond (CB), G-Premio Bond (GP), Prelude One (PO) and Scotchbond Universal (SB). The reactivity on polished substrates was evaluated by reflection infrared microscopy (RFTIRM). The roughness parameters of polished and 50 μm alumina grit-blasted surfaces were assessed by optical profilometry. The SBS of the composite bonded to the substrates treated with each adhesive (n = 10/product) was evaluated after 1 week of storage (H2O/37 °C) by Weibull statistics. Evidence of phosphate interaction with polished substrates was obtained by FTIRM, with higher peaks on the alloy. Alumina-blasting increased all roughness parameters with higher values on the alloy. AD, CB were the strongest (σ0) treatments on alloy surfaces and AD, CB, AB, SB on zirconia. GP was the weakest on both substrates and the least reliable (β) on alloy. On polished alloy GP, PO performed better (σ0), whereas on zirconia there were no significant differences. All adhesives showed more prominent reaction with the Co-Cr alloy than with 3Y-TZP.